Ectodermal Dysplasia: An Overview - Sruti Prava Panda (Institute of Medico-legal Publications Pvt Ltd, 2020)
Ectodermal dysplasia is a rare hereditary disorder with a characteristic physiognomy. It is a genetic disordermainly striking the growth or purpose of the teeth,hair, nails and sweat glands. Ectodermal dysplasia canalso affect the skin, the lens or retina of the eye, partsof the inner ear, the growth of fingers and toes, thenerves and other parts of the body providing to thes pecific syndrome. All the syndrome generallyinvolves adifferent combination of symptoms, which can range from mild to severe. The antiquity andlessons learnedfrom hypohidrotic ectodermaldysplasia (HED) can serve as an example for investigating the root andpathogenesis of other ectodermal dysplasia syndromes by denoting that phenotypically identical syndromescan be caused by mutations in different genes, mutations in the same gene can lead to different phenotypesand that mutations in the genes further ensue in the same indicating pathway may alter the phenotype quiteprofoundly. This paper aims to describe and discuss the etiology, genetic review, clinical manifestations andtreatment options of this hereditary disorder.